KUALITAS PELAYANAN PUBLIK DI KANTOR CAMAT RUMBAI PESISIR - eka, eka (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
Public services at the district office coastal fringe. The quality of public services can be measured include the following elements: the turnaround time of service, details of fees or tariffs, procedures, facilities and infrastructure. In the implementation of public services in the district during the coastal fringe still constraints in implementing the four elements of the charter, because of the lack of openness to the public, although the sub-district officials had to undertake socialization activities that also involve the public. Although officially a maximum service is 15 minutes, the findings in the field expressed ketidaksusuaian with what has been set. The factors that affect the quality of services at the district office coastal fringe is: 1. Work Motivation bureaucracy and apparatus; 2. The ability of the apparatus; 3.pengawasan / social control; 4. The behavior of bureaucracy / apparatus; 5. Communication, disposition and bureaucratic structure and organizational communication climate and the flow of information; and 6. Restructuring the organization.